THE ROLE OF HUMAN RESOURCE MANAGEMENT ON INCREASING ORGANIZATIONAL COMMITMENT TO HOSPITAL EMPLOYEES IN BANYUMAS REGENCY - Mastur Mujib Ikhsani; Fatmah Bagis; Akhmad Darmawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The research aims to find out the extent of the role of human resource management, from the point of view of employee training and development, work environment, and compensation at An Ni'mah Wangon General Hospital. The survey method used in this research uses a quantitative study. Respondents in this study were employees of the An Ni'mah Wangon Regional General Hospital who were permanent employees and did not belong to the nutrition and security services division. The sample used in this study was 100 employees who were then analyzed using Partial Least Square (PLS) analysis. The results of the analysis show the acceptance of Human resource management influences organizational commitment. The results shows that training and development has a significant effect on organizational commitment. The results of the analysis also show that the work environment has a significant influence on organizational commitment. The results are different for the compensation variable, the compensation has not significant effect on organizational commitment. Keywords: Organizational Commitment, Human resource management, work environment, training and development.